2006
DOI: 10.1093/jnci/djj010
|View full text |Cite
|
Sign up to set email alerts
|

Incident High-Grade Squamous Intraepithelial Lesions in Senegalese Women With and Without Human Immunodeficiency Virus Type 1 (HIV-1) and HIV-2

Abstract: HIV-1 and HIV-2 are associated with increased risk for development of HSIL. This risk appears to be associated primarily with increased HPV persistence that may result from immunosuppression related to HIV-1 and/or HIV-2 infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
66
2
11

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(85 citation statements)
references
References 41 publications
6
66
2
11
Order By: Relevance
“…Comparable studies using PCR-based detection of HPV in HIV-infected women have reported 12 -79% of study participants with multiple HPV types (Levi et al, 2002;Moscicki et al, 2004;Bollen et al, 2006;Didelot-Rousseau et al, 2006;Hawes et al, 2006;Luque et al, 2006). This high prevalence may reflect the immune impairment by HIV that fails to clear HPV, leading to chronic HPV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Comparable studies using PCR-based detection of HPV in HIV-infected women have reported 12 -79% of study participants with multiple HPV types (Levi et al, 2002;Moscicki et al, 2004;Bollen et al, 2006;Didelot-Rousseau et al, 2006;Hawes et al, 2006;Luque et al, 2006). This high prevalence may reflect the immune impairment by HIV that fails to clear HPV, leading to chronic HPV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Six et al 21 , em estudo comparativo entre mulheres positivas e negativas para o HIV, obtiveram prevalências de SIL de 31,3 e 7,5%, respectivamente, resultados mais significativos do que os de Schuman et al 22 , que salientaram prevalências respectivas de 19 e 5%, e os de Singh et al 23 , com resultados de 15,9 e 1,5%, utilizando a citologia oncótica para o diagnóstico. No que diz respeito somente a mulheres positivas para o HIV, estudo africano utilizando a citologia encontrou prevalência de SIL de 12,3% 24 , enquanto o estudo chinês já citado, também utilizando a citologia oncótica, e incluindo ASCUS, encontrou 16% de SIL 20 . Estudos brasileiros utilizando a biópsia de colo uterino registraram prevalência de NIC de 23,4% em 494 mulheres HIV-positivas do Estado de Minas Gerais 25 , e de 18% em 255 mulheres HIV-positivas na cidade de São Paulo 26 .…”
Section: Métodosunclassified
“…A prevalência de infecção cervical pelo HPV é mais alta nas mulheres positivas para o HIV, com índices variando na literatura de 34 a 98% 20,[22][23][24][25][26][29][30][31] . Metanálise envolvendo 5.578 pacientes com HIV positivo com citologia oncótica normal em vários países encontrou média de prevalência de infecção pelo HPV de 36,3%, sendo que os mais altos índices foram nas Américas do Sul e Central: 56,6% 32 .…”
Section: Métodosunclassified
“…In our study, the risk of CIN21 and CIN31 among WLWH compared to HIV negative women was larger than expected from several earlier reports. 4,[18][19][20][21] This high risk was driven by the large discrepancy in risk between migrants with and without HIV. Surprisingly, little is known regarding the risk of CIN21 and CIN31 among migrant women living with HIV from countries with high incidence of cervical cancer.…”
Section: Discussionmentioning
confidence: 99%